Learning Analytics to Improve the Quality of Decision-Making in Digital Education - Ali Mashari; Sulistianah Sulistianah; Oktri Wulandari (PT. Anagata Sembagi Education, 2026)
This study aims to analyze the role of Learning Analytics in improving the quality of decision-making in digital education. A quantitative descriptive-analytical design was employed. The respondents consisted of educators and digital learning managers directly involved in the use of learning data and educational decision-making. Data were collected through a questionnaire measuring the level of Learning Analytics utilization and decision-making quality. Descriptive analysis was conducted to identify patterns in the relationship between Learning Analytics utilization and decision-making quality. The results indicate that higher utilization of Learning Analytics is associated with more rational, accurate, and useful educational decisions. These findings highlight the role of Learning Analytics as an essential support tool for data-driven and evidence-based decision-making in digital education